Smart Shallot Farming: Prototype of Internet of Thing (Iot)-Based Shallot Farming System as a Sustainable Agricultural Innovation - Darmono; Khakam Ma’ruf; Yanuar Agung Fadullah; Bagus Putra Setiyawan; Surono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The shallot commodity is an important agricultural commodity for the food economy, its price often experiences a high increase especially when entering the dry season. The current constraints of shallot farming spend more time and energy because the whole process is done manually which makes farmers experience losses and incur more costs. To overcome these obstacles, researchers innovate to offer Smart Shallot Farming, this system can be applied to shallot farming to simplify and save the cost of maintaining shallot plants. This innovation in shallot farming will simplify and save the cost of shallot plant maintenance. The application of Salfarm on shallot farming is expected to be a technological innovation to improve national resilience in agriculture.